Pengembangan Sistem Analisis Butir Soal Ujian berbasis Web (Studi Kasus: SMP Negeri 1 Donomulyo) - Retno Inten Fitria Febri; Achmad Arwan; Faizatul Amalia (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Item analysis is an activity carried out by the teacher which aims to determine the level of student understanding and improve the quality of the questions that have been made. Most of the teachers carried out the item analysis activities at Public Junior High School 1 Donomulyo using the excel program and others manually,in both ways the time needed to carry out the item analysis was quite long. That is because the teacher has to enter student answer data into the excel program one by one to process analysis. As an effort to overcome these problems, an item analysis system was developed to make easier for teacher to carry out item analysis. The main function of this system is to be able to generate the item analysis based on the exam that students has taken. The system is built on a web platform using waterfall development method and object-oriented approach. The system is implemented with Codeigniter framework for the back-end side which supports Model View Controller (MVC) concepts and the Bootstrap framework for the front-end side. The system test results was 100% valid in unit testing, integration testing, and validation testing, which means that the system is in accordance with defined needed. In addition, the system also tested using compatibility testing which showed that system was compatible with several browsers tested.